Past and current asbestos exposure and future mesothelioma risks in Britain: The Inhaled Particles Study (TIPS). (9th March 2018) - Gilham, Clare; Rake, Christine; Hodgson, John; Darnton, Andrew; Burdett, Garry; Peto Wild, James; Newton, Michelle; Nicholson, Andrew G; Davidson, Leslie; Shires, Mike; Treasure, Tom; Peto, Julian; et al.
Abstract: Background: Occupational and environmental airborne asbestos concentrations are too low and variable for lifetime exposures to be estimated reliably, and building workers and occupants may suffer higher exposure when asbestos in older buildings is disturbed or removed. Mesothelioma risks from current asbestos exposures are therefore not known. Methods: We interviewed and measured asbestos levels in lung samples from 257 patients treated for pneumothorax and 262 with resected lung cancer, recruited in England and Wales. Average lung burdens in British birth cohorts from 1940 to 1992 were estimated for asbestos-exposed workers and the general population. Results: Regression analysis of British mesothelioma death rates and average lung burdens in birth cohorts born before 1965 suggests a lifetime mesothelioma risk of approximately 0.01% per fibre/mg of amphiboles in the lung. In those born since 1965, the average lung burden is ∼1 fibre/mg among those with no occupational exposure. Conclusions: The average lifetime mesothelioma risk caused by recent environmental asbestos exposure in Britain will be about 1 in 10 000. The risk is an order of magnitude higher in a subgroup of exposed workers and probably in occupants in the most contaminated buildings. Further data are needed to discover whether asbestos still present in buildings, particularly schools, is a persistent or decreasing hazard to workers who disturb it and to the general population, and whether environmental exposure occurs predominantly in childhood or after beginning work. Similar studies are needed in other countries to estimate continuing environmental and occupational mesothelioma hazards worldwide, including the contribution from chrysotile.